Kisah Nabi Luth dan Kaum Sodom dalam Al-Qur'an (Analisis Semiotika Saussure dan A.J. Greimas) - Syam, Ishmatul Karimah; Taufiq, Wildan; Solehudin, Solehudin (Jurnal Penelitian Ilmu Ushuluddin, 2023)
This research aims to examine more deeply the study of semiotics on the story of people who were doomed in the Qur'an, one of them being the Sodomites. Examining the values and messages conveyed through the signs and symbols in the story with a semiotic approach initiated by Ferdinand de Saussure in the form of signifiers and signifieds, syntagmatic and paradigmatic relations. As well as with the narrative semiotic approach initiated by A.J. Greimas in describing the storyline of the Prophet Luth. This study uses a descriptive-analytic method which is based on qualitative data about the story of Prophet Luth and the people of Sodom in the Qur'an using the semiotic approach of Saussure and A.J Greimas. Many studies of the Qur'an have begun to be carried out using a semiotic approach in its interpretation. Deeper research on one of the stories in the Qur'an with a semiotic approach will lead us to many lessons and reveal the secrets behind the symbols and signs that exist in it. The result of this research is, it is found that the story of Prophet Luth and his people in the Qur'an is repeated many times by Allah with different verses and different storylines. In fact, it is part of the symbol that repetition occurs to give its respective purpose in several different places and as a complement to one another. Likewise, with Saussure's theory, there are many symbols and signs that God sent to commemorate them as well as us. The actions they commit are called heinous acts because they are the same as adultery, so the punishment for them according to fiqh scholars is the same as haad for adultery. As well as the narrative story of Prophet Luth which is more directed in a more directed manner with the Greimas narrative. Then the teachings and moral messages from the story of Prophet Luth can be wisdom and lessons for the people after him. This research is still limited to symbols in general, so future research can reveal symbols and signs and the secrets behind the language and every word in the verse.